2009
DOI: 10.1002/sim.3710
|View full text |Cite
|
Sign up to set email alerts
|

Randomization by minimization for unbalanced treatment allocation

Abstract: Minimization is a dynamic randomization technique that has been widely used in clinical trials for achieving a balance of prognostic factors across treatment groups, but most often it has been used in the setting of equal treatment allocations. Although unequal treatment allocation is frequently encountered in clinical trials, an appropriate minimization procedure for such trials has not been published. The purpose of this paper is to present novel strategies for applying minimization methodology to such clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 10 publications
0
108
0
2
Order By: Relevance
“…Randomization by minimization was applied, including gender, age, and medication use as factors (Han, Enas, & McEntegart, 2009). Randomization was performed using a computerized program (MACRO™) provided by the Clinical Trials Unit at King's College, London, once families gave their consent.…”
Section: Methodsmentioning
confidence: 99%
“…Randomization by minimization was applied, including gender, age, and medication use as factors (Han, Enas, & McEntegart, 2009). Randomization was performed using a computerized program (MACRO™) provided by the Clinical Trials Unit at King's College, London, once families gave their consent.…”
Section: Methodsmentioning
confidence: 99%
“…For example, randomization by minimization has been proposed by Taves [15]. Some recent advances in this area can be found in references [16,17].…”
Section: Summary and Discussionmentioning
confidence: 98%
“…The chosen treatment could simply be taken as the one with the lower score or a random element could be introduced [1]. It is customary to introduce a random element to make the allocations more unpredictable [5]; the preferred treatment is assigned with a higher allocation probability, and non-preferred treatments are given low probabilities [5, 6]. In practise, one has to select that p (i.e., allocation probability) which strikes a balance between minimising treatment imbalance and avoiding predictability of treatment assignment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [6] showed that the minimisation process needs to be modified for trials involving unbalanced or unequal treatment allocations. Authors introduced two modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation